2016
DOI: 10.1017/jfm.2016.808
|View full text |Cite
|
Sign up to set email alerts
|

Wake structure and thrust generation of a flapping foil in two-dimensional flow

Abstract: We present a combined numerical (particle vortex method) and experimental (soap film tunnel) study of a symmetric foil undergoing prescribed oscillations in a two-dimensional free stream. We explore pure pitching and pure heaving, and contrast these two generic types of kinematics. We compare measurements and simulations when the foil is forced with pitching oscillations, and we find a close correspondence between flow visualisations using thickness variations in the soap film and the numerically determined vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(81 citation statements)
references
References 32 publications
11
70
0
Order By: Relevance
“…Although the reverse von Kármán vortex street is the most commonly encountered wake vortex pattern, many other patterns are possible. In figure 3 we have sketched some of the patterns observed in the experiments and computations of [10]; even more exotic patterns have been observed. With wildly varying wake patterns, we may expect to see large differences in swimming performance as the wake transitions from one pattern to another.…”
Section: Third Case: Vortex Pattern and Interactionsmentioning
confidence: 91%
See 2 more Smart Citations
“…Although the reverse von Kármán vortex street is the most commonly encountered wake vortex pattern, many other patterns are possible. In figure 3 we have sketched some of the patterns observed in the experiments and computations of [10]; even more exotic patterns have been observed. With wildly varying wake patterns, we may expect to see large differences in swimming performance as the wake transitions from one pattern to another.…”
Section: Third Case: Vortex Pattern and Interactionsmentioning
confidence: 91%
“…Conclusions regarding thrust based on the vertical spacing of vortices are inaccurate, however. Generally speaking, the drag-thrust transition occurs when the wake is already a "thrust-type" wake [10], since some excess streamwise fluid momentum is needed to overcome profile drag or velocity fluctuations and pressure differences in the control volume [11,12]. Furthermore, even "drag-producing" wakes have been observed to produce thrust [10].…”
Section: First Case: Vortex Spacingmentioning
confidence: 99%
See 1 more Smart Citation
“…This was also supported by Taylor et al (2003) and Triantafyllou et al (1993) who observed that the majority of natural fliers and swimmers prefer to cruise within this range. According to Andersen et al (2017), BvK reversal occurs at different St A values for pure heave and pure pitch. Therefore, St A cannot be regarded as an expression of self similarity.…”
Section: Introductionmentioning
confidence: 99%
“…The article by Andersen et al (2017) presents a detailed and revealing investigation of the rich variety of wake structures of a flapping wing, and relates the changes in the wake structure to the transition from drag to thrust.…”
Section: Overviewmentioning
confidence: 99%